Fault Lines in China's Economic Terrain - Wolf, Charles Jr (RAND Corporation, 2003)
The authors consider how and by how much China's stellar economic performance might be impaired by eight potential adversities that China may face in the next decade: unemployment, poverty, and social unrest; corruption; HIV/AIDS and epidemic diseases; water resource problems and pollution; energy consumption and prices; the fragile financial system and state-owned enterprises; curtailed foreign direct investment; and serious military conflicts.